ANALISIS FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM SEKTOR PERDAGANGAN STUDI KASUS TOKO KELONTONG DI DENPASAR SELATAN - Antara, I Made Suda; Wenagama, I Wayan (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 12 (2023): Vol.12.No.12. DESEMBER 2023DO - 10.24843/10.24843/EEP.2023.v12.i12.p05, 2023)
The existence of a grocery store is not difficult to find (usually strategically located), this is because large capital ownership helps traders increase the variety of merchandise so that it is easy to develop in urban areas. Therefore, the existence of this grocery store can be said to be a supporter of the economy. This research will further examine the factors that influence the income of grocery stores in Denpasar City, which are seen from the capital factor, location, type of merchandise, and business length simultaneously and partially. The population used is grocery store traders in South Denpasar, with a sample of 100 respondents who were directly surveyed. The data collected was then analyzed using multiple linear regression analysis. The findings show that there is a simultaneous effect of capital, location, type of merchandise, and length of business on the income of grocery stores in South Denpasar. Partially, the variable capital and length of business partially have a positive and significant effect on the income of grocery stores in Denpasar City, while the amount of merchandise has a positive but not significant effect. The income of grocery store traders with strategic locations is higher than those with non-strategic locations. The variable that has the strongest influence on the income of grocery stores in South Denpasar is capital. Followed by the location variable in second place, and the length of business variable with the weakest influence keyword : capital, firm location, income, market Klasifikasi JEL: D24, R3, P36, E44